The Origins of the Term Distance Education and the Roots of Digital Teaching and Learning - Olaf Zawacki-Richter (The Canadian Network for Innovation in Education (CNIE), 2024)
By no means is the digitalization of learning and teaching a new phenomenon (cf. Inglis, et al., 1999). Since the 1960s and 70s, open and distance teaching universities have spearheaded new and emerging technologies to bridge the distance between students and teachers. Since the turn of the millennium, online learning has spread worldwide, particularly in countries with a long tradition of distance education (e.g., Canada, Australia, India, or South Africa, see Qayyum & Zawacki-Richter, 2018; Zawacki-Richter & Qayyum, 2018). Online study programs have also been increasingly established at campus-based universities. In 1999, Alan Tait observed that the boundaries between distance teaching and conventional campus-based universities were blurring: "The secret garden of open and distance learning has become public, and many institutions are moving from single conventional mode activity to dual mode activity" (Tait, 1999, p. 141).